Nuclear medicine meets radiation therapy - Schütze, C.; Krause, M.; Yaromina, A.; Zips, D.; Baumann, M. (Nuklearmedizin - NuclearMedicine, 2010)
Radiobiological and cell biological knowledge is increasingly used to further improve local tumour control or to reduce normal tissue damage after radiotherapy. Important research areas are evolving which need to be addressed jointly by nuclear medicine and radiation oncology. For this differences of the biological distribution of diagnostic and therapeutic nuclides compared with the more homogenous dose-distribution of external beam radiotherapy have to be taken into consideration. Examples for interdisciplinary biology-based cancer research in radiation oncology and nuclear medicine include bioimaging of radiobiological parameters characterizing radioresistance, bioimage-guided adaptive radiotherapy, and the combination of radiotherapy with molecular targeted drugs.
Keywords: Radiotherapy; tumour stem cells; tumour hypoxia; biological image guided radio-therapy; molecular targeting